Immobilization of Thalassospira profundimaris M02 for Improved Biotransformation of Heterocyclic Hydrocarbon Compounds - Intan Mariana, Maliki (Universiti Malaysia Sarawak (UNIMAS), 2020)
Heterocyclic hydrocarbon compounds are known as by-products for various industries and has become a threat of contamination in the environment. Bioremediation was applied to solve this problem. However, high toxicity levels tend to inhibit the performance of the bacteria for biodegradation of the compounds. Cell immobilization technique was developed and applied to resolve this issue. This study aimed to develop and investigate the performance of immobilized cell in comparison to free cells in the degradation of heterocyclic hydrocarbon compounds such as carbazole (CAR), dibenzofuran (DBF), dibenzothiophene (DBT) and fluorene (FL). In this study, the optimal cell immobilization conditions of isolated marine bacteria, T. profundimaris strain M02 was immobilized by using calcium alginate at 4% (w/v) concentration with cell mass loading of 1.25 g. These developed immobilized cells were also able to be used repetitively although depletion of the cell’s performance was observed. On other hand, T. profundimaris strain M02 was able to degrade multiple heterocyclic hydrocarbon compounds and showed significant performance improvement when immobilized. Actual performance test was carried out in bioreactor and from the test, both free and immobilized cells showed improved performance in a controlled environment in the bioreactor when compared to the laboratory scale experiment. Comparative study of free and immobilized cell performance in bioreactor showed that immobilized cells exhibited higher concentration of CAR degraded as well as higher specific growth rate. To conclude, the findings of this study discovered the optimum conditions for bacteria immobilization for heterocyclic hydrocarbon compounds degradation as well as revealing that a single bacteria strain are able to degrade multiple compounds. This information is important as it can be utilized for biodegradation of heterocyclic hydrocarbon compounds in the environment and improved the existing technique that is currently implemented today.